32+3(x-4)=8x-40

Simplify each term.

Apply the distributive property.

32+3x+3⋅-4=8x-40

Multiply 3 by -4.

32+3x-12=8x-40

32+3x-12=8x-40

Subtract 12 from 32.

3x+20=8x-40

3x+20=8x-40

Subtract 8x from both sides of the equation.

3x+20-8x=-40

Subtract 8x from 3x.

-5x+20=-40

-5x+20=-40

Subtract 20 from both sides of the equation.

-5x=-40-20

Subtract 20 from -40.

-5x=-60

-5x=-60

Divide each term in -5x=-60 by -5.

-5x-5=-60-5

Cancel the common factor of -5.

Cancel the common factor.

-5x-5=-60-5

Divide x by 1.

x=-60-5

x=-60-5

Divide -60 by -5.

x=12

x=12

Solve for x 32+3(x-4)=8x-40